(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The aims of this paper to identify the determinants of self-sufficiency in fish wealth in Jordan during the period 2002-2022, and to identify the water resources available for fish farming and fishing, feasible investment opportunities, and the geographical distribution of water resources that can be used, such as artesian wells, springs, dams, lakes, etc. The descriptive and quantitative statistical analysis methods adopted in building economic analysis models, for simple and multiple regression, and testing the effect of independent variables on the dependent variable (self-sufficiency). Measuring the strength of the correlation and the direction of the positive and negative relationship of the variables under study, the most important of which are: local production, net imports, the consumer price index, population size, per capita consumption rate, number of fishing boats, disposable of consumption, etc. The average self-sufficiency rate for various types of fish in Jordan was approximately 5%. Imported fish constitutes 95% of the total available for consumption in the local market. The per capita fish consumption rate is estimated at 3.7 kg/year in Jordan, compared to about 11 kg/year in the Arab world. Self-sufficiency is affected by a positive relationship with variables such as local production, net imports, and the consumer price index, and a negative relationship with population size and per capita consumption. This is consistent with the theoretical concept of the strength and direction of the expected relationship. The most important recommendation is to support the efforts of planners and food security policymakers towards the investment in utilizing the available natural and human resources, to increase local production of various types of fish. Providing production requirements for fish farming and fishing at low prices.